2017
DOI: 10.1111/obr.12536
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of interval training versus moderate‐intensity continuous training on body adiposity

Abstract: Interval training (including high-intensity interval training [HIIT] and sprint interval training [SIT]) is promoted in both scientific and lay media as being a superior and time-efficient method for fat loss compared with traditional moderate-intensity continuous training (MICT). We evaluated the efficacy of HIIT/SIT when directly compared with MICT for the modulation of body adiposity. Databases were searched to 31 August 2016 for studies with exercise training interventions with minimum 4-week duration. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
186
4
36

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(241 citation statements)
references
References 83 publications
15
186
4
36
Order By: Relevance
“…However, similar energy expenditure over 24 h has been observed following HIIT and MICT [29]. Furthermore, recent systematic reviews and meta-analyses have shown that HIIT and MICT can induce similar improvements in body adiposity, with HIIT possibly being a more "time-efficient" exercise strategy [30,31]. Although, as seen in the present review, when HIIT or MICT are performed on their own without any dietary intervention, it is unlikely that clinically meaningful weight loss (>5% reduction [32]) in body mass and body fat can be achieved unless performed at very high volumes [33].…”
Section: Discussionmentioning
confidence: 85%
“…However, similar energy expenditure over 24 h has been observed following HIIT and MICT [29]. Furthermore, recent systematic reviews and meta-analyses have shown that HIIT and MICT can induce similar improvements in body adiposity, with HIIT possibly being a more "time-efficient" exercise strategy [30,31]. Although, as seen in the present review, when HIIT or MICT are performed on their own without any dietary intervention, it is unlikely that clinically meaningful weight loss (>5% reduction [32]) in body mass and body fat can be achieved unless performed at very high volumes [33].…”
Section: Discussionmentioning
confidence: 85%
“…Nesse sentido, o HIIT proporcionou respostas comparáveis aos do CONT, exigindo um comprometimento ~20% menor no tempo, indicando possibilidade de prescrição/implementação na gestão da obesidade e sobrepeso [8][9][10] . Entretanto, Keating et al 21 relatam que os resultados obtidos com a utilização do HIIT como estratégia para o controle da gordura corporal ainda são controversos, o que corroboramos com os achados desta meta-análise. Foi observado que o grupo CONT mostrou superioridade estatistica na redução da circunferência de cintura de 1,19 cm em relação as reduções obtidas pelo HIIT, tendo uma diminuição total de aproximadamente de 3cm.…”
Section: Discussionunclassified
“…Foram observadas respostas similares entre HIIT e CONT para os niveis de gordura corporal e circunferência da cintura. Keanting et al 21 , também relataram encontrar resposta similar após avaliarem 31 ensaios clínicos randomizados e não randomizados. A superioridade do CONT no desfecho circunferência da cintura encontrada em nosso estudo pode estar associada a exclusão de ensaios clínicos não randomizados, porém, os autores Wewege et al 20 e Keating et al 21 optaram por incluir estudos com essa característica metodológica.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Yet, from the present data it is actually unclear whether caloric expenditure was higher in the HIIT arm compared to the MCT arm. Earlier meta-analyses 17,18 performed in obese patients clearly demonstrated that when training protocols were not matched, EE was usually less in HIIT compared to MCT. In patients with CAD, Pattyn et al 19 measured the EE of HIIT and MCT programmes as planned in the SAINTEX-CAD study (based on Wisloff et al), 9,20 and the actually performed training intensities.…”
mentioning
confidence: 99%